Assessment of technical and biological parameters of volumetric quantitative computed tomography of the foot: a phantom study - Smith, K. E.; Whiting, B. R.; Reiker, G. G.; Commean, P. K.; Sinacore, D. R.; Prior, F. W. (Osteoporosis international, 2012)
Summary Few studies exist for bone densitometry of the whole foot. A phantom study demonstrated the sources of error and necessary controls for accurate quantitative computed tomography of the foot. A loss in bone mineral density (BMD) in the small foot bones may be an early indicator of diabetic foot complications. Introduction Volumetric quantitative computed tomography (vQCT) facilitates the assessment of pedal bone osteopenia, which, in the presence of peripheral neuropathy, may well be an early sign of diabetic foot deformity. To date, sources and magnitudes of error in foot vQCT measurements have not been reported. Methods Foot phantoms were scanned using a 64-slice CT scanner. Energy (in kilovoltage peak), table height, phantom size and orientation, location of “bone” inserts, insert material, location of calibration phantom, and reconstruction kernel were systematically varied during scan acquisition. Results Energy (in kilovoltage peak) and distance from the isocenter (table height) resulted in relative attenuation changes from −5% to 22% and −5% to 0%, respectively, and average BMD changes from −0.9% to 0.0% and −1.1% to 0.3%, respectively, compared to a baseline 120-kVp scan performed at the isocenter. BMD compared to manufacturer-specified values ranged, on average, from −2.2% to 0.9%. Phantom size and location of bone-equivalent material inserts resulted in relative attenuation changes of −1.2% to 1.4% compared to the medium-sized phantom. Conclusion This study demonstrated that variations in kilovoltage peak and table height can be controlled using a calibration phantom scanned at the same energy and height as a foot phantom; however, error due to soft tissue thickness and location of bones within a foot cannot be controlled using a calibration phantom alone.